2017
DOI: 10.2514/1.c032919
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic Model for Macrofiber Composite Actuators on Micro Air Vehicles

Abstract: The main focus of this research is the generation of a computational aeroelastic model for a macrofiber composite actuated micro air vehicle. Two M8528-P1 actuators were used to deform the surface of a forward-swept thin, compliant composite wing. The general approach, which included MATLAB, ABAQUS, and Athena Vortex Lattice, is described. The planform design and initial flight testing are discussed. The computational model was validated first with static tests, and then quasi-static wind-tunnel tests were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A ply stack of MFC and unidirectional carbon fiber was used in this partition. Strain values presented by LaCroix and Ifju (2017) using thermal analogy, which represents a change in voltage on the MFC as a virtual increase in temperature in the FEA, were used to implement the MFC actuation strain into the FEA. The boundary condition used for this model was a fixed condition on one end based on the cantilever setup.…”
Section: Fea Model Of Mfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…A ply stack of MFC and unidirectional carbon fiber was used in this partition. Strain values presented by LaCroix and Ifju (2017) using thermal analogy, which represents a change in voltage on the MFC as a virtual increase in temperature in the FEA, were used to implement the MFC actuation strain into the FEA. The boundary condition used for this model was a fixed condition on one end based on the cantilever setup.…”
Section: Fea Model Of Mfcsmentioning
confidence: 99%
“…The MFC embedded wing actuated a third of the roll moment compared to conventional ailerons but was adequate for roll control of the planned MAV. LaCroix and Ifju (2017) investigated the application of two M8528-P1 MFC actuators for maximum pitch and roll authority on a forward-swept MAV. Bilgen et al (2009) explored the control authority of MFCs on a variable camber-controlled MAV with a wingspan of 2.5 ft. (0.76 m).…”
Section: Introductionmentioning
confidence: 99%
“…The most modern active elements considered in various types of research are Macro Fiber Composite (MFC) elements which have recently found many interesting applications. In papers [1,2], the design and practical applications of MFC elements are presented. The author of [3] described and investigated the properties of MFC elements.…”
Section: Introductionmentioning
confidence: 99%